2017
DOI: 10.1159/000486167
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Reduction in Myocyte Autophagy After Myocardial Infarction in Rabbits: Association with Oxidative Stress and Left Ventricular Remodeling

Abstract: Background/Aims: The alterations in myocyte autophagy after myocardial infarction (MI) and the underlying mechanisms have not been fully understood. In this study, we investigated the temporal changes of myocyte autophagy in the remote non-infarcted myocardium in rabbits after MI and the relationships between alterations of myocyte autophagy and left ventricular (LV) remodeling and myocardial oxidative stress. Methods: Rabbits were assigned to MI or sham operation. Rabbits with MI or sham were randomly assigne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Following cardiac injury regardless of cause, oxidative stress contributes critically to pathological remodeling by fibrosis and the ensuing increased proarrhythmic risk at fibrotic border zones. Notably, increased oxidative stress to the heart may occur specifically post-infarction (Ide et al, 2001;Venditti et al, 2001;Carpi et al, 2009;Chi et al, 2017;Margaritis et al, 2017) and in heart failure (Nickel et al, 2015;Bertero and Maack, 2018b;Zhou and Tian, 2018). However, increased oxidative stress to the heart may also occur non-specifically in cardiac inflammation (Zhou et al, 2011), metabolic dysregulation (Nickel et al, 2015;Bertero and Maack, 2018a), and aging (Ander et al, 2007;Lisanti et al, 2011;Martín-Fernández and Gredilla, 2016).…”
Section: Dual Hits By Fibrosis and H 2 O 2 For Arrhythmogenic Synergymentioning
confidence: 99%
“…Following cardiac injury regardless of cause, oxidative stress contributes critically to pathological remodeling by fibrosis and the ensuing increased proarrhythmic risk at fibrotic border zones. Notably, increased oxidative stress to the heart may occur specifically post-infarction (Ide et al, 2001;Venditti et al, 2001;Carpi et al, 2009;Chi et al, 2017;Margaritis et al, 2017) and in heart failure (Nickel et al, 2015;Bertero and Maack, 2018b;Zhou and Tian, 2018). However, increased oxidative stress to the heart may also occur non-specifically in cardiac inflammation (Zhou et al, 2011), metabolic dysregulation (Nickel et al, 2015;Bertero and Maack, 2018a), and aging (Ander et al, 2007;Lisanti et al, 2011;Martín-Fernández and Gredilla, 2016).…”
Section: Dual Hits By Fibrosis and H 2 O 2 For Arrhythmogenic Synergymentioning
confidence: 99%
“…The role of autophagy after MI is still controversial. Chi et al found that myocyte autophagy progressively decreased at 1, 4, and 8 weeks after MI, 23 but Yan et al found that the LC3-II/I ratio and Beclin 1 increased in chronic ischemic myocardium. 24 Mice with per2 overexpression showed high expression levels of LC3 (Fig.…”
Section: Overexpression Of Per2 Increases Myocardial Autophagy After MImentioning
confidence: 99%
“…Myocardial infarct size was measured as described previously 30,31 . For the hearts used for biochemical assays, infarct size was estimated from the ratio of the infarct to the whole LV weights.…”
Section: Methodsmentioning
confidence: 99%